Diagnostic yield of FAP-guided positron emission tomography in thyroid cancer: a systematic review - Rizzo, Alessio; Albano, Domenico; Dondi, Francesco; Cioffi, Martina; Muoio, Barbara; Annunziata, Salvatore; Racca, Manuela; Bertagna, Francesco; Piccardo, Arnoldo; Treglia, Giorgio (Frontiers in Medicine, 2024)
Background Several recent studies have proposed the possible application of positron emission tomography/computed tomography (PET/CT) administering radiolabelled fibroblast-activation protein (FAP) inhibitors for various forms of thyroid cancer (TC), including differentiated TC (DTC), and medullary TC (MTC). Methods The authors conducted an extensive literature search of original studies examining the effectiveness of FAP-guided PET/CT in patients with TC. The papers included were original publications exploring the use of FAP-targeted molecular imaging in restaging metastatic DTC and MTC patients. Results A total of 6 studies concerning the diagnostic yield of FAP-targeted PET/CT in TC (274 patients, of which 247 DTC and 27 MTC) were included in this systematic review. The included articles reported high values of FAP-targeted PET/CT detection rates in TC, ranging from 81 to 100% in different anatomical sites and overall superior to the comparative imaging method. Conclusion Although there are promising results, the existing literature on the diagnostic accuracy of FAP-guided PET in this context is still quite limited. To thoroughly evaluate its potential significance in TC patients, it is needed to conduct prospective randomized multicentric trials.